L’éducation esthétique pour soutenir le rôle de médiateur culturel : quelles retombées sur les enseignants et les artistes ? - Beaudry, Marie-Christine; Crête-Reizes, Marika; Lemonchois, Myriam; Carignan, Isabelle (Canadian Journal of Education/Revue canadienne de l’éducation, 2024)
Acting as a cultural facilitator is expected of Quebec teachers and artists called upon to intervene with students. However, many say they are poorly equipped to perform this role. In order to support teachers and artists in their role as cultural facilitators, we set up an action-research study. The research pursued the general objective of offering training to teachers and artists in aesthetic education, an approach used in the United States to support teachers and artists as cultural facilitators. Consisting of six meetings, the training aimed to disseminate to the participants what aesthetic education is and to lead them to create and experiment with activities in class based on this approach. We followed the eight participants (two teachers, six artists) in order to describe the influence of aesthetic education on their understanding of their role as cultural facilitators and on their professional practice. The qualitative data were collected through semi-structured interviews, a report on each meeting, a logbook, and activities created by the participants. The thematic analysis made it possible to identify two main results: aesthetic education confirmed and enriched the professional practice of the participants and changed, for some, the representations they have of their role as cultural facilitator.